2008
DOI: 10.1136/oem.2008.041376
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of respiratory and cardiovascular hospital admissions to the southern California wildfires of 2003

Abstract: Objective There is limited information on the public health impact of wildfires. The relationship of cardiorespiratory hospital admissions (n = 40 856) to wildfire-related particulate matter (PM2.5) during catastrophic wildfires in southern California in October 2003 was evaluated. Methods Zip code level PM2.5 concentrations were estimated using spatial interpolations from measured PM2.5, light extinction, meteorological conditions, and smoke information from MODIS satellite images at 250 m resolution. Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
427
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 396 publications
(450 citation statements)
references
References 42 publications
18
427
4
1
Order By: Relevance
“…No association was found with wildfire smoke and ischemic heart disease hospitalizations in California, while another study found an increase in clinic‐based ischemic heart disease visits among Native Americans of the Hoopa tribe of northern California 43, 44. An Australian study mentioned earlier found increased rates of hospital admissions and ED visits for ischemic heart disease among women and adults aged >65 years at lag day 2 15…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…No association was found with wildfire smoke and ischemic heart disease hospitalizations in California, while another study found an increase in clinic‐based ischemic heart disease visits among Native Americans of the Hoopa tribe of northern California 43, 44. An Australian study mentioned earlier found increased rates of hospital admissions and ED visits for ischemic heart disease among women and adults aged >65 years at lag day 2 15…”
Section: Discussionmentioning
confidence: 94%
“…Elsewhere, heart failure‐related ED visits were elevated in the context of peat bog fires in North Carolina in 2008, but the association was not significant when repeated for fires in 2011 and only suggestive among wildfires in 1 study from California 15, 16, 26, 43, 45. Other cardiovascular outcomes, such as cardiac dysrhythmia, or pulmonary embolism, have not been found to have a clear association with wildfire‐PM 2.5 , although some suggestive effects have been found for dysrhythmia 26, 43, 46. This investigation contributes to those significant findings of dysrhythmia and pulmonary embolism, but no association was found with peripheral arterial disease, potentially because of a small number of related ED visits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we defined 6-8 July 2002 as our haze period, when air pollution was also at its highest and compared it to a control non-haze period, corresponding to the same days of the preceding week (29,30 June and 1 July 2002). We chose not to include the same days in the following week as part of the control because of potential persisting effects in the post-haze period [19] The same days of the week were used in this fashion to minimize potential time-varying confounding effects, such as might be expected for weekday versus weekend. Within our period of interest, we observed a total of 5772 for all respiratory hospital admissions, and 18,316 hospital admissions for all cardiovascular hospital admissions.…”
Section: Resultsmentioning
confidence: 99%
“…Short-term exposures to fine particulate matter, PM 2.5 (airborne particulate matter with aerodynamic diameter of ≤2.5 µm) have been associated with increased mortality and morbidity in various communities around the world and in the United States [19][20][21][22][23][24][25][26][27][28]. Most studies addressing health impacts of short-term exposures are related to anthropogenically generated PM, which are commonly associated with automobile combustion and industrial practices.…”
Section: Introductionmentioning
confidence: 99%